Accumulation of mineral nutrients in fruit peel and pulp of loquat (Eriobotrya japonica) cultivars during fruit developmental stages - RADHIKA, JAKKULA; BONS, HARSIMRAT K (The Indian Journal of Agricultural Sciences, 2024)
The experiment was conducted during 2023 at Punjab Agricultural University, Ludhiana, Punjab to assess the changes of mineral nutrients in peel and pulp of loquat cultivars at four developmental stages to explore its nutraceutical potential. During the development of loquat fruits, K and Zn content both in peel and pulp showed increasing trend from 60–92 DAFS. Similarly, Ca content in loquat peel, Fe and Mn content in pulp also exhibited increasing trend. While P, Cu and Mg content showed a decreasing trend in both peel and pulp. Likewise, Ca content in loquat pulp, Fe and Mn content in peel decreased from 60–92 DAFS. This study provides an insight regarding the accumulation of mineral nutrients in fruit peel and pulp in loquat cultivars during four fruit developmental stages which could be helpful for exploring its nutraceutical potential.